Positive psychological changes and associated factors among community health workers post-COVID-19 in China: a mixed-methods study - Qingyu Li; Yuhang Zhang; Jiaruo Sun; Jingtao Zhou; Siwen Huang; Liqun Wu; Wannian Liang; Jiming Zhu; Huatang Zeng; Sitong Luo (Frontiers in Public Health, 2026)
Background Community health workers (CHWs) played an important role in community-based COVID-19 prevention and control while maintaining routine primary care. The pandemic created a stressful work context for CHWs and may also have been followed by perceived positive psychological changes. Although positive psychological changes have been studied among hospital-based healthcare workers, less is known about such changes among CHWs in China. This study assessed self-reported positive psychological changes and associated factors among Chinese CHWs after the COVID-19 pandemic. Methods A mixed-methods study was conducted from April 29 to June 10, 2023, in Shenzhen, China. In the quantitative phase, cluster sampling was used to recruit CHWs from 51 community health centers. Participants completed an online survey on demographic characteristics, COVID-19-related exposure, rumination, coping strategies, perceived social support, and positive psychological changes. Moderate-to-high positive psychological changes were defined as a mean item score of ≥3 in at least one domain of the Chinese version of the Post-Traumatic Growth Inventory. Univariate and multivariable logistic regression analyses were performed. In the qualitative phase, purposive sampling was used to recruit CHWs for semi-structured interviews, and interview data were analyzed using interpretative phenomenological analysis. Results The quantitative phase included 634 CHWs. The mean age was 35.7 years, and 76.0% were female. Overall, 58.8% reported moderate-to-high positive psychological change. After adjustment, moderate-to-high positive psychological change was associated with higher positive coping (AOR = 1.13, 95% CI: 1.08–1.18), deliberate rumination (AOR = 1.12, 95% CI: 1.06–1.18), and family support (AOR = 1.08, 95% CI: 1.02–1.14). Sensitivity analysis showed similar patterns, although some associations differed between the models. The qualitative phase included 12 CHWs from 6 community health centers. Interviews further suggested that coping strategies, cognitive processing, family support, and work-related support shaped their psychological adjustment. Conclusion More than half of CHWs reported moderate-to-high positive psychological change after the COVID-19 pandemic. Workplace mental health programs for CHWs should address distress while supporting adaptive coping, reflective processing of difficult work experiences, and family-sensitive support. These measures may help protect CHWs’ mental health and improve primary care preparedness for future public health emergencies.